Corporate income tax contribution of the polish financial sector - Wojciech Stiller (e-Finanse: Financial Internet Quarterly, 2018)
The financial crisis has stimulated the debate on the taxation of the financial sector. The focus is on the bank levy and financial transaction tax, whereas corporate income tax attracts less attention in the public debate. Accordingly, this study analyses the contribution of the financial sector to Polish revenue from corporate income tax. Based on tax statistics of the Ministry of Finance from 1998 to 2016, the aggregated effective tax burden of the financial sector is determined and compared with the tax burden of corporations from other sectors. In addition, the study deals with loss deduction of the financial sector in comparison to non-financial corporations. The study shows that the effective tax burden of the financial sector - measured as a ratio of the tax due to income - is higher than the corresponding burden for corporations from outside this sector. A higher corporate income tax burden of the financial sector also applies if it is measured by aggregated profits reduced by losses. An exception to this is the period up to 2002 and the year 2009, when the effective tax burden of the financial sector was lower after the inclusion of losses when compared to other sectors of the Polish economy. This can be explained by the relatively low losses of the Polish financial corporations compared to other corporations.
Keywords: E62; G20; H25; 330; corporate income tax; effective tax burden; financial sector; Poland; tax revenue